The Influence of Price Perception, Product Quality, Reviews, and Trust on Online Purchase Intention in Handicraft MSMEs - Irenetia, Nina; Luthfia, Amia; Hadiyati, Istia Ayu (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The development of information and communication technology has transformed digital marketing practices among Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the factors that influence consumer purchasing intention in handicraft products online, focusing on price perception, product quality, consumer reviews, and trust. The research method used is quantitative with a survey approach. Data was collected through a questionnaire distributed to 389 respondents. The analysis was conducted using regression techniques to test the influence of inter-variables on purchase intention. The results of the study show that product quality, price perception, consumer trust, and consumer reviews have a positive influence on purchase intention, with product quality having the strongest influence. This suggests that consumers prioritize price-quality considerations over reviews or trust when making purchasing decisions. Accordingly, MSMEs should focus on marketing strategies that emphasize product quality and competitive pricing, as well as improving quality consistency and pricing to strengthen online purchase appeal through more effective and targeted digital promotion strategies.